Dentinal tubule occluding capability of nano‐hydroxyapatite; The in‐vitro evaluation. Issue 8 (29th April 2018) - Baglar, Serdar; Erdem, Umit; Dogan, Mustafa; Turkoz, Mustafa
Abstract: In this in‐vitro study, the effectiveness of experimental pure nano‐hydroxyapatite (nHAP) and 1%, 2%, and 3% F¯ doped nano‐HAp on dentine tubule occlusion was investigated. And also, the cytotoxicity of materials used in the experiment was evaluated. Nano‐HAp types were synthesized by the precipitation method. Forty dentin specimens were randomly divided into five groups of; 1—no treatment (control), 2—specimens treated with 10% pure nano‐HAp and 3, 4, 5 specimens treated with 1%, 2%, and 3% F − doped 10% nano‐HAp, respectively. To evaluate the effectiveness of the materials used; pH, FTIR, and scanning electron microscopy evaluations were performed before and after degredation in simulated body fluid. To determine cytotoxicity of the materials, MTT assay was performed. Statistical evaluations were performed with F and t tests. All of the nano‐HAp materials used in this study built up an effective covering layer on the dentin surfaces even with plugs in tubules. It was found that this layer had also a resistance to degradation. None of the evaluated nano‐HAp types were have toxicity. Fluoride doping showed a positive effect on physical and chemical stability until a critical value of 1% F − . The all evaluated nano‐HAp types may be effectively used in dentin hypersensitivity treatment. The formed nano‐HAp layers were seem to resistant to hydrolic deletion. The pure and 1% F − doped nano‐HAp showed the highest biocompatibility thus it was assessed that pure and 1% F − doped materials may be used as an active ingredient in dentin hypersensitivity agents. Abstract : We have observed that nano‐hydroxyapatite types which are produced by precipitation method can also be used effectively as dentinal tubule occluding agents to treat dentin hypersensitivity instead of commercially available ones. The produced pure and fluoride doped nano hydroxyapatite layers on the dentin surfaces were resistant to in vitro degradation and were non toxic. Increasing the amount of fluoride doping also resulted in increasing the adhesion on the dentin surface.